Święty Konstantyn cesarz w obrazowej polemice z ikonoklastami. Kilka słów refleksji o miniaturze w Psałterzu Chłudowa z IX wieku .......... 65 - Smorąg-Różycka, Małgorzata (Plus ultra: Studia z historii sztuki ofiarowane Profesorowi Markowi Walczakowi w 60. rocznicę urodzin, 2025)
SAINT EMPEROR CONSTANTINE IN A VISUAL POLEMIC WITH THE ICONOCLASTS: SEVERAL REFLECTIONS ON A MINIATURE FROM THE 9TH-CENTURY CHLUDOV PSALTER Amongst the iconographic program of the Byzantine-Ruthenian paintings in the royal chapel at Lublin Castle (1418), scholars have long been intrigued by the figure of a knight on a white horse, accompanied by an angel offering him a crown and a cross mounted on a tall shaft, depicted on the northern wall of the triumphal arch separating the presbytery from the nave. In this depiction, scholars have identified the coat of arms of Lithuania, the figure of the patron of the paintings, King Władysław II Jagiełło or Saint Ladislaus I of Hungary, and, more recently, even the Roman Emperor Constantine the Great. The motif of the cross prompted to consider the “apostolic” mission of the Christianisation of Lithuania (1387) undertaken by Jagiełło. For this reason, the king was compared to Emperor Constantine the Great. This association was not unknown to the king’s contemporaries, being mentioned, among others, in the well-known speech of Sigismund of Luxembourg delivered at the Council of Constance in February 1418. A few months later, the paintings in the Lublin chapel, including the composition discussed here, were completed. Since in the discussion on the “Constantinian” symbolism of the Lublin fresco the miniature from the Chludov Psalter (fol. 59v) from around the mid-9th century was cited, the present article is devoted to the interpretation of this image and to the role of the Constantinian legend in the iconoclastic discourse in Byzantium. The miniature depicts Emperor Constantine on horseback, repelling the attack of three archers, and refers to the words of Psalm 59:6, written in the first lines at the top of the folio. This image is not merely a literal illustration of the psalm’s words but has a deeper meaning, which the painter (or scribe?) guides the viewer to discern by introducing a graphic sign in the form of a small curved line with a dot, painted in blue above the word ή σημείωσις (“sign”) and above the cross crowning Constantine’s spear. This also allows one to conjecture that the depiction of Constantine in the Chludov Psalter conveys meanings that go beyond the historical and symbolic significance of Constantine’s vision framed around his battlefield triumph under the sign of the cross. In the course of the iconoclastic discourse, the sign of the cross from the imperial vision became one of the most important arguments against images, which, as was claimed, should have been replaced. Under these circumstances, an urgent need emerged among the iconodules to oppose attempts by the iconoclasts to appropriate the Constantinian legend. In response, the iconodules, in emphasising that the opposition of “cross versus image” was false, made a fundamental distinction: the sign of the cross is worthy of veneration because of Christ’s Passion and death, whereas the icon is the true image of the Incarnate Logos. In this way, the small miniature in the Chludov Psalter became a part of this discourse through the inclusion of subtle graphic signs within a seemingly banal scene.